Analisis swot untuk menentukan strategi bersaing saat masa pandemi covid-19 pada rumah sakit islam surabaya - Elvana, Yesia; Hariyati, Hariyati; Setianto, Budhi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study has a goal, namely to find out the right competitive strategy using SWOT analysis at the Surabaya Islamic Hospital so that its business can be even better, able to attract interest and give trust to the public regarding the health services it has, can measure and determine the right management at the Surabaya Islamic Hospital so that it can encourage business progress in the face of increasingly fierce competition even during the Covid-19 pandemic. The type of research used is descriptive qualitative. The data analysis technique in this research is SWOT (Strength, Weakness, Opportunity, Threat) analysis. The results of the study showed that in the Internal Factors Analysis Summary (IFAS) the total score for the strength factor was 5.89, and the weakness was 2.47, then in the External Factors Analysis Summary (EFAS) the total score for the opportunity was 4.46, and the threat was 4. ,20. From these results, the SWOT diagram at the Surabaya Islamic Hospital is in quadrant I (one), namely the aggressive and supportive strategy using the SO (Strength-Opportunity) strategy.